The COVID-19 impact on statistical learning at State Islamic University in East Indonesia. (October 2020) - Nisa, K; Mujizatullah, M; Idham, I; Nawawi, M I; Darwis, D; Amiruddin, A; Israpil, I; Arsyad, A R
Abstract: This research aims to describe the portrait of statistical learning before COVID-19 at State Islamic University in east Indonesia, the transformation of the blended learning to full e-learning in statistical courses as the impact of the COVID-19, as well as the challenges and opportunities of statistical courses with full e-learning in COVID-19 situations. The type of this research is descriptive qualitative. Data obtained by telephone interviews with five lecturers from State Islamic University in east Indonesia. The data analysis technique consists of data reduction, data display, and verification. The results of this research show that lecturers have applied e-learning in statistics courses at State Islamic University before the COVID-19. Although face to face learning methods is more dominant used in statistical courses than e-learning methods. The dominant learning media used by lecturers in statistics courses during COVID-19 are WhatsApp and Google Classroom. The biggest challenges faced at statistical courses by e-learning systems are the availability of a stable internet network, and some students do not have personal computers and even mobile phones. As good news, this situation can challenge lecturers and students to be more literate and accustomed to technology. Some lecturers even make YouTube account to support statistical learning.